Stakeholder Management in Designing CSR Activities: The Case of Bank Islam - Abu Bakar, Fathiyyah; Md Yusof, Mohd 'Atef (Journal of Business Management and Accounting, 2016)
CSR  commitments  should  be  viewed  from  a  broad  Islamic  perspective  of  reducing poverty rate, and enhancing quality of Muslims’ lives. The purpose of this study was to determine how Bank Islam manages its stakeholders, and their issues, in designing CSR activities through the three level of maslahah. A group of CSR players at the bank has been interviewed together with on-field observations as well as documentation reviews  to  gain  insights  into  the  process  of  managing  stakeholders.  The  findings indicated that the bank acknowledges the importance of managing stakeholders, and their  issues,  through  the  engagement  of  various  CSR  activities.  In  designing  CSR activities, the process of identifying the stakeholders and their issues may need to be carefully examined to improve the impact of the activities on the recipients. This study offers a new insight to the body of knowledge of CSR from the Islamic perspectives of stakeholder management.
Keywords: Corporate social responsibility (CSR); Islamic bank; case study; stakeholder management